Over-the-Counter Medication Use without Prescription Trends in Dhaka City: A Cross-Sectional Survey (Medicine Today, 2025)
Introduction: Self-medication with over-the-counter (OTC) drugs is rising in urban Bangladesh, raising concerns over misdiagnosis, side effects, and antibiotic resistance. Data on such practices among diverse adult populations in Dhaka City remain limited. Objectives: To estimate the prevalence of OTC medication, use without prescription, identify motivations, characterize ailments and drug categories, and examine demographic predictors. Methods: A cross-sectional survey was conducted from March to May 2025 among 400 adults in Dhaka using multistage cluster sampling. A semi-structured questionnaire captured demographic data, self-medication practices, types of ailments, drug classes, sources, motivations, and knowledge. Data were analyzed using descriptive statistics, chi-square tests, and logistic regression. Results: Of 400 participants (mean age 26.5 ± 8.3 years; 52% female), 83.0% reported self-medication in the past three months. Major reasons included quick relief (40.0%), lack of time (27.5%), minor illness perception (21.3%), and high consultation cost (16.8%). Common ailments were fever/headache (24.8%), gastric issues (22.3%), and respiratory symptoms (14.0%). Frequently used OTC drugs included NSAIDs (33.0%), antacids (20.5%), antibiotics (17.5%), and antipyretics (13.0%). Pharmacies were the main source (78.3%), with influences from peers (45.1%) and old prescriptions (42.2%). Male gender, higher education, and student status were significant predictors (p < 0.05). Conclusions: OTC self-medication is highly prevalent in Dhaka, driven by convenience and accessibility. Misuse of NSAIDs and antibiotics signals urgent need for regulatory control, public education, and affordable healthcare options.Medicine Today 2025, Vol.37 (2): 252-257